The Theory of Structural Anomie and Law Breaking: Case of Ahvaz’s Scientific Applied University (Iran) - Khedry Leila; Hosseyni Maryam; Salehi Shablizi Massod; Bani Naimeh Isa; Moshtaghi Ali (Budapest International Research and Critics University, 2020)
This study aimed to explain law breaking with applying structural theory of anomy. To do this, relationship between individuals, achievement orientation, universalism and money fetishism as four indexes of cultural successfulness, with law breaking from one side, and relationship between socio-economic status(SES) from two objective and subjective dimensions with law breaking as well as structural anomy and its components were examined. The applied method was survey and 400 people were selected randomly among the students. The questionnaires which used in the study included three instruments: structural anomy scale, socio- economic status questionnaire, and law breaking tendency questionnaire. A positive significant relationship between structural anomy and law breaking was found. Results showed that the effect of individuals and money fetishism on law breaking is significant; however the effect was not appeared for achievement orientation and universalism. No significant relationship was found between law breaking and SES. The achieved relationship between objective SES and structural anomy was positive but weak. In sum, it can be said that the theory can explain law breaking phenomena properly.